PUTUSAN PRAPERADILAN PENGADILAN NEGERI SINTANG NOMOR : 01/PID.PRAP/2015/PN.STG MEMENANGKAN TERMOHON YANG MELAKUKAN PENANGKAPAN DAN PENAHANAN YANG TIDAK SESUAI DENGAN KETENTUAN KUHAP - DAMIANUSN DEDY SUSANTO, SH A.2021131030, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses pretrial about the arrests and detentions in relation to the rights of the accused under the Criminal Code (Studies Pretrial Sintang District Court Decision No. 01 / Pid.Prap / 2015 / PN.Stg). The method used in this research is normative juridical approach. From the results of this thesis can be concluded that the function of pretrial within the scope of the jurisdiction of Sintang has been running optimally. Pretrial case that was last recorded in the District Court pretrial Sintang is the case with the Sintang District Court No. 01 / Pid.Prap / 2015 / PN.Stg. And after that there are no more cases of pretrial incoming afterwards. This shows that the implementation of the pre-trial functions has been running well in controlling horizontally between relevant law enforcement authorities such as judges, public prosecutors and the police. In addition praeradilan maximal function can also be on the performance of judges, or police as an investigator or prosecutor as a public prosecutor under examination in accordance with the procedures set out in the Act - legislation. Every action or forceful measures undertaken such as the arrest, detention, seizure, search, and others - others have been carried out in accordance with the law. But in practice often encountered effort or coercive measures that violate the provisions of the Act - legislation. This is due to the lack of information and knowledge about the existence of this pretrial institution and its function and purpose. This is exploited by elements investigators that